Probiotics in Disease Prevention and Treatment - Liu, Yuying; Tran, Dat Q; Rhoads, J Marc (Journal of clinical pharmacology, 2018)
Few treatments for human diseases have received as much investigation in the past 20 years as probiotics. In 2017, English-language meta-analyses totaling 52 studies determined the effect of probiotics on conditions ranging from necrotizing enterocolitis and colic in infants to constipation, irritable bowel syndrome, and hepatic encephalopathy in adults. The strongest evidence in favor of probiotics lies in the prevention or treatment of 5 disorders: necrotizing enterocolitis, acute infectious diarrhea, acute respiratory tract infections, antibiotic-associated diarrhea, and infant colic. Probiotic mechanisms of action include the inhibition of bacterial adhesion; enhanced mucosal barrier function; modulation of the innate and adaptive immune systems (including induction of tolerogenic dendritic cells and regulatory T cells); secretion of bioactive metabolites; and regulation of the enteric and central nervous systems. Future research is needed to identify the optimal probiotic and dose for specific diseases, to address whether the addition of prebiotics (to form synbiotics) would enhance activity, and to determine if defined microbial communities would provide benefit exceeding that of single-species probiotics.